Editorial. Issue 1 (1st March 2016) - Wilkinson, Nicholas
Abstract : The 40th year of publication of Open House International is now complete. That means one hundred and sixty manuscripts have been published since the journals inception forty years ago. To keep standards high we impose strict regulations for writing and we wish to see that there is always a clear and understandable focus to the subject at hand. In the application of this approach approximately seventy five percent of the manuscripts received are rejected each quarter whilst the remaining twenty five percent continue on to the production and final publication stage.